Pomiar nieinwazyjny - metody i wiarygodność osiąganych wyników - Chełpa, Stanisław (Non-reactive measures: methods and credibility of the results, 2006)
The article presents six fundamental methods employed in non-reactive measuring of organizational phenomena and processes. Non-reactive measurement methods require that a researcher refrains from interfering with an object which undergoes research, also persons scrutinized are not aware of being subject to research. It has also been remarked that the credibility of research conducted in accordance with this approach greatly depends on experience and skills of a researcher and on utilizing methodological triangulation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 23-29